2021
DOI: 10.1177/00219096211034882
|View full text |Cite
|
Sign up to set email alerts
|

How Farming Communities Cope With Displacement Arising from Farmer-Herder Conflict in North Central Nigeria

Abstract: A largely overlooked area in extant literature on farmer-herder conflict in Nigeria is coping strategies employed by internally displaced farming communities. Using exploratory design and qualitative data collection tools, we collected data from 23 purposively selected victims of farmer-herder conflict in Nasarawa State who were displaced and were either living in internally displaced persons camps or with friends/family. Findings showed that participants relied on their friends and family to cope with victimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…However, some studies have examined the lived experiences of communities that choose to remain in their conflict-affected villages, which require them to pay taxes and conform to the rules imposed by nonstate actors controlling their communities (de Montclos, 2020; Higazi, 2016). The few studies on immobility in Nigeria have concentrated on people’s experiences in Internally displaced person’s (IDPs) camps and other camp-like settings (see Ogbozor, 2016; Shehu & Abba, 2020; Yikwab & Tade, 2022).…”
Section: Immobility In North Central Nigeriamentioning
confidence: 99%
“…However, some studies have examined the lived experiences of communities that choose to remain in their conflict-affected villages, which require them to pay taxes and conform to the rules imposed by nonstate actors controlling their communities (de Montclos, 2020; Higazi, 2016). The few studies on immobility in Nigeria have concentrated on people’s experiences in Internally displaced person’s (IDPs) camps and other camp-like settings (see Ogbozor, 2016; Shehu & Abba, 2020; Yikwab & Tade, 2022).…”
Section: Immobility In North Central Nigeriamentioning
confidence: 99%
“…Female farmers did not go to their farms when herders were spotted grazing around them for fear of being sexually assaulted or killed . Some farmers decided to reduce their farming and engage in supplemental off-farm income-generating activities (Yikwab and Tade 2021).…”
Section: Passivementioning
confidence: 99%
“…The victimisation challenges facing displaced people have been explored in several studies. For instance, a study conducted in North-Central Nigeria (Yikwabs and Tade, 2021) examined the strategies employed by IDPs who are victims of farmer–herder conflict to cope with the effects of their victimisation. The study found that IDPs employed various coping strategies, including social support, religious beliefs, and self-reliance.…”
Section: Literature Reviewmentioning
confidence: 99%